Legal Protection for Religious Foundations Over Land Ownership Certificates Granted - Iqbal, Muhammad (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
This study aims to determine and analyze the legal protection of religious foundations for land grant certificates and to determine and analyze the legal procedures for religious foundations to obtain land grant certificate status. The research approach method used in this thesis is the normative legal research method. The specifications of this study use normative legal research. The types of data used in this study are primary data including the 1945 Constitution;civil law book, compilation of Islamic law, basic law on agrarian principles, PP no. 38 of 1963, and ATR/BPN head regulation no. 2 in 2013, as well as secondary data containing books and other supporting documents. Data collection research with document study research techniques or library materials. The data analysis method used in analyzing the data is qualitative analysis, namely the inventory of primary and secondary legal materials in a structured manner. The results of the study will describe the results of the Research and discussion consisting of; Regulation of legal protection for religious foundations for land grant certificates, and Legal procedures for religious foundations to obtain land grant certificate status.